Interregional cooperation in the Rhine-Alpine Corridor - Jörg Saalbach (Border Futures - Zukunft Grenze - Avenir Frontière: The future viability of cross-border cooperation, 2022)
Cross-border, transnational regional development in the Rhine-Alpine EU transport corridor represents an ongoing challenge. With 18 partners from five countries, the Rhine-Neckar regional association (Verband Region Rhein-Neckar, VRRN) therefore initiated an EU-funded project along the corridor to tackle the task. The INTERREGfinanced project used the acronym 'CODE24' and developed a joint strategy for developing the Rhine-Alpine Corridor from the perspective of the regional-municipal level. To ensure the continuation of this successful cooperation beyond the running time of the project, a new, permanent organisation was founded: the Interregional Alliance for the Rhine-Alpine Corridor. A European Grouping for Territorial Cooperation (EGTC) was chosen as the legal form. The organisation was founded on 24 April 2015 in Mannheim and was the first EGTC established in Germany, which now comprises 19 members.
urn:nbn:de:0156-40971451; hdl:10419/258994; https://econpapers.repec.org/RePEc:zbw:arlabe:33
Keywords: 710; INTERREG; CODE24; Rhine-Alpine Corridor; EGTC; Interregional Alliance for the Rhine-Alpine Corridor